Pengembangan Kualitas Pendidikan di Kabupaten Tapanuli Utara Berbasis Inovasi: Analisis SWOT - Pardomuan Simanullang; Noverius Lase; Rosnia Sianturi; Elises Tambunan; Ringhot Simorangkir (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze innovation-based strategies for improving the quality of education using a SWOT approach. Innovation is understood as the process of generating new ideas and implementing relevant solutions to enhance the effectiveness of learning and educational governance. The study employs a qualitative approach with a descriptivestrategic method through literature review and contextual analysis of regional education conditions. The findings indicate that North Tapanuli Regency possesses several strengths, including government commitment, teacher competence, and strong local cultural support. However, weaknesses such as disparities in school quality, low digital literacy, and unequal distribution of facilities remain significant challenges. Opportunities arising from national policies and technological developments are widely accessible, while threats such as economic inequality and rapid technological changes pose serious challenges. The study concludes that educational development strategies must be implemented systematically through SO, WO, ST, and WT strategies, with emphasis on digitalization, teacher competency enhancement, data-based management, and cross-sector collaboration.